Tanggapan dan Tantangan Public Relations Menghadapi Hoaks : Studi Deskriptif Kualitatif pada Public Relations Rumah Sakit Akademik UGM - Arfan Kalendra Garvi Wardana; Sri Hastjarjo; Ign. Agung Satyawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The rise of hoaxes is currently increasingly undirected, along with the rapid growth of information and communication technology. In almost all aspects of life, hoaxes appear. The topic of health is not free from hoax news. Public officials are also often involved in reporting hoaxes related to health. Public Relations of RSA UGM as one of the pilot hospitals also took part in explaining the existence of health hoaxes. RSA UGM Public Relations took action to resolve this problem. This research analyzes how RSA UGM's public relations strategy responds to health hoaxes. The analysis was carried out using Ronald D. Smith's (2005) concept of public relations strategy which is divided into proactive strategies and reactive strategies. The results of the research show that in responding to health hoaxes, RSA UGM Public Relations recruits carried out preventive efforts well in advance in the form of proactive action and communication on their social media. When hoaxes emerged, RSA UGM Public Relations through its social media accounts provided education and adopted reactive strategies to respond to turmoil in society. In carrying out a strategy to respond to hoaxes, RSA UGM Public Relations relies more on social communication media than conventional communication media.